Differential Expression of Wnt Pathway Genes in Sporadic Hepatocellular Carcinomas Infected With Hepatitis B Virus Identified With OligoGE Arrays - Lin, Xiaoyan (Kowsar, 2013)
BACKGROUND: Epidemiological evidence has clearly indicated that chronic infection with the hepatitis B virus (HBV) is the major risk factor for developing hepatocellular carcinoma (HCC). Nonetheless, the mechanisms by which HBV contributes to the pathogenesis of HCC have not been fully elucidated. OBJECTIVES: Our aim was to characterize differential gene expression profiles related to the Wnt signaling pathway between primary tumor and adjacent normal tissues in HCC patients with concomitant HBVinfection . MATERIALS AND METHODS: An oligoGEArray® (an oligonucleotide-based gene expression array platform) containing 126 Wnt signaling pathway-related genes was used to compare gene expressions between primary HCC and adjacent non-tumorous liver tissues from 10 patients with HCC. Selected differential genes were identified with real-time RT-PCR and immunohistochemistry (IHC). In particular, the protein of the differential gene DVL3 (disheveled, dsh homolog 3 [Drosophila]) was chosen to investigate whether it is up regulated in primary tumor correlated with the clinic pathological characteristics of HCC patients. For this purpose we examined 56 HCC tissue samples via IHC for the presence of DVL3 protein. RESULTS: Sixteen genes were identified with significant differential expression between HCC and adjacent non-tumorous liver tissue. These genes have been previously associated with the Frizzled signaling pathway, cell cycle, transcription, or protein degradation. All (100%) of the tumor samples results from 56 HCC patients tested were positive for DVL3 via IHC. Based on the intensity of DVL3 immunoreactivity, 25 (44.6%) and 31 (55.4%) of the patients were classified aslow and high-DVL3, respectively, which correlated with tumor stage (P = 0.029). CONCLUSIONS: This study clarified a number of Wnt pathway-related genes which are dysregulated in HBV-associated HCC. These genes may be contributedto the frequent activation of the Wnt signaling pathway. Our results promote the role of the Wnt signaling pathway in HBV-associated HCC.